Dietary Inclusion of Organic Chromium on Production and Carcass Characteristics of Broilers - Anandhi, M.; Mathivanan, R.; Viswanathan, K.; Mohan, B. (International Journal of Poultry Science, 2006)
An experiment was conducted to study the influence of dietary organic chromium on production and carcass characteristics of broilers for a period of six weeks with one hundred and twenty eight commercial, straight run day-old broiler chicks. These chicks were randomly grouped into four treatments with four replicates of eight chicks each. The treatment groups consisted of basal diet (T1), 250 (T2), 500 (T3) and 750 (T4) μg organic chromium per kilogram basal diet. The results revealed no significant difference in body weight gain, feed consumption, feed conversion ratio, and livability between treatment groups from first week to the end of the experimental period. The carcass yields did not differ between treatment groups. The abdominal fat-pad thickness was significantly (P< 0.05) reduced in chromium-supplemented groups. However, moisture and ether extract content of breast and thigh muscle did not differ significantly between the treatment groups. However, the breast and thigh muscle protein levels were significantly (P< 0.05) increased in 500 and 750 μg organic chromium supplemented groups compared to control. Breast and thigh muscle cholesterol was significantly lower (P< 0.05) in chromium-supplemented groups as compared to the control group. Based upon the study, the supplementation of organic chromium in broiler ration did not improve the production performance. However, it may be used to produce lean meat.